Drought Stress and its Effect on Amazonian forest Dynamics Model Projections - Karfakis, T. N. S.; Andrade, A.; Volkmer-Castilho, C.; Valle, D. R.; Arets, E.; Gardingen, P. Van (International Journal of Bio-resource and Stress Management, 2023)
The large diversity of tree species of tropical moist forests relative to temperate zones and their biomass storage capacity and how these are maintained over extended periods of time have been subjects of particular interest. Simulation models of forest dynamics are increasingly used to gain insights regarding the long term effect of both direct and indirect anthropogenic impacts on these forests. If such models cannot maintain a stable coexistence of species and biomass dynamics in undisturbed forest simulations modeling results might be misleading with potentially deleterious implications. An effort is described, based on a nested experimental design by use of simulation modeling and examination of long term permanent sample plots data (PSP’s) along with climatic records that had the objective to assess the importance of periodic drought disturbance in the maintenance of compositional and biomass stability over a 100-year period on the dynamics of the primary forest and on the sustainability of timber harvesting in the tropical non flooded forests of the Amazon basin. This is done using two separately recalibrated models within the SYMFOR modeling framework. It is shown that periodic drought stress within the limits of natural environmental fluctuation can have a significant influence on the simulated biomass dynamics of these forests considering trees>10 cm dbh but not on the dynamics of functional composition. Implications of these were found to be highly significant.